New insights into the crust and lithospheric mantle structure of Africa from elevation, geoid, and thermal analysis - (:unkn) unknown (My University, 2016)
Abstract We present new crust and lithosphere thickness maps of the African mainland based on integrated modeling of elevation and geoid data and thermal analysis. The approach assumes local isostasy, thermal steady state, and linear density increase with depth in the crust and temperature‐dependent density in the lithospheric mantle. Results are constrained by a new comprehensive compilation of seismic Moho depth data consisting of 551 data points and by published tomography models relative to LAB depth. The crustal thickness map shows a N‐S bimodal distribution with higher thickness values in the cratonic domains of southern Africa (38–44 km) relative to those beneath northern Africa (33–39 km). The most striking result is the crustal thinning (28–30 km thickness) imaged along the Mesozoic West and Central African Rift Systems. Our crustal model shows noticeable differences compared to previous models. After excluding the Afar plume region, where the modeling assumptions are not fulfilled, our model better fits the available seismic data (76.3% fitting; root mean square error = 4.3 km). The LAB depth map shows large spatial variability (90 to 230 km), with deeper LAB related to cratonic domains and shallower LAB related to Mesozoic and Cenozoic rifting domains, in agreement with tomography models. Though crustal and lithosphere thickness maps show similar regional patterns, major differences are found in the Atlas Mountains, the West African Rift System, and the intracratonic basins. The effects of lateral variations in crustal density as well as the nonisostatic contribution to elevation in the Afar plume region, which we estimate to be ~1.8 km, are also discussed.
Keywords: African Research